Ultraviolet curing glue as well as preparation method and application thereof

By preparing a specific composition of ultraviolet curing glue, the problem that existing UV glue is difficult to take into account both flexibility and tensile strength is solved, and more efficient pattern transfer and injection molding quality is achieved in the IMR injection molding process.

CN119823695APending Publication Date: 2025-04-15WUHAN HUAGONG IMAGE TECH & DEV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510120634.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-26
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing UV glues are difficult to take into account both flexibility and tensile strength, which may lead to unsuccessful injection molding or poor product appearance in the IMR injection molding process.

Method used

An ultraviolet curing glue is used to form 15 to 25 parts of aliphatic polyurethane acrylate with a carbon number of 4 to 8, 15 to 25 parts of polyester acrylate, 10 to 15 parts of long-carbon chain aliphatic polyurethane acrylate with a carbon number of 12 to 18, 2 to 6 parts of silane coupling agent modified vapor phase silica, 30 to 35 parts of bifunctional acrylate monomer, 5 to 10 parts of trifunctional acrylate monomer and 4 to 8 parts of photoinitiator, and is prepared by specific mixing and stirring steps.

Benefits of technology

This ultraviolet curing glue has excellent flexibility and high tensile strength, and can achieve rapid curing, good adhesion and efficient pattern transfer in the preparation of IMR diaphragm, significantly improving the injection molding quality and finished product decoration effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823695A_ABST
    Figure CN119823695A_ABST
Patent Text Reader

Abstract

The invention provides ultraviolet curing glue as well as a preparation method and application thereof, and belongs to the technical field of adhesives. The ultraviolet curing glue is prepared from the following components in parts by mass: 15 to 25 parts of aliphatic polyurethane acrylate with the carbon atom number of 4 to 8, 15 to 25 parts of polyester acrylate, 10 to 15 parts of long-carbon-chain aliphatic polyurethane acrylate with the carbon atom number of 12 to 18, 2 to 6 parts of silane coupling agent modified fumed silica, 30 to 35 parts of bifunctional acrylate monomer and 5 to 10 parts of trifunctional acrylate monomer, and 4-8 parts of a photoinitiator. The ultraviolet curing glue has the characteristics of high curing speed, high adhesive force and excellent flexibility and tensile strength. When the ultraviolet curing glue is used for preparing an IMR membrane, a pattern with a better effect can be shown to the greatest extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to an ultraviolet curing glue and a preparation method and application thereof. Background Art

[0002] UV molding technology is a processing technology that uses ultraviolet light curing technology to achieve 3D graphic surface processing. This technology forms a pre-designed 3D pattern in the mold, presses the mold with ultraviolet light curing resin, and when ultraviolet light is irradiated to the surface of the ultraviolet light curing resin, the resin is quickly cured and the pattern on the mold is transferred to the resin surface. This technology has the advantages of high precision, high efficiency, low cost, energy saving and environmental protection, and wide applicability. It has been widely used in the production of packaging and anti-counterfeiting labels in many industries such as furniture, automobiles, and electronic products.

[0003] IMR (In-Mould Decoration by Roller) film includes a base film, a pre-coating layer and a UV holographic layer stacked in sequence. After injection molding, the pattern on the UV holographic layer is transferred to the surface of the injection molded part. In some IMR injection molding processes, the IMR film is used as the mother film, and the pattern on the mother film is stretched, bent and completely transferred to the injection molded part, and finally the mother film is separated from the injection molded part. UV glue is a key factor in ensuring the smooth injection molding of IMR products. Poor flexibility or tensile strength of UV glue on the base film may lead to unsuccessful injection molding or poor product appearance. This will seriously affect the decorative effect of the finished product and have an adverse effect on the experience of later use.

[0004] Using aliphatic oligomeric polyurethane acrylate or polyester acrylate as the main resin can generally make the coating prepared by UV glue have better flexibility. Adding a crosslinking agent to the resin to increase the crosslinking density of the UV glue coating, thereby improving the tensile strength and hardness of the UV glue coating is a common method at present. However, although increasing the crosslinking density of the UV glue coating can improve its tensile strength and hardness, it will cause the UV glue coating to become too rigid and reduce flexibility. Therefore, it is difficult for existing UV glues to achieve both flexibility and tensile strength. Summary of the invention

[0005] Based on the above problems, the present invention provides a UV curing glue and a preparation method thereof. The UV curing glue has both excellent flexibility and high tensile strength.

[0006] Specifically, in order to achieve the above purpose, the present invention adopts the following technical solutions: A UV curing glue comprises the following components in parts by mass: 15-25 parts of aliphatic polyurethane acrylate with 4-8 carbon atoms, 15-25 parts of polyester acrylate, 10-15 parts of long carbon chain aliphatic polyurethane acrylate with 12-18 carbon atoms, 2-6 parts of silane coupling agent modified fumed silica, 30-35 parts of difunctional acrylate monomer, 5-10 parts of trifunctional acrylate monomer and 4-8 parts of photoinitiator.

[0007] In a preferred embodiment, the aliphatic polyurethane acrylate having 4 to 8 carbon atoms is any one of difunctional aliphatic polyurethane acrylate, trifunctional aliphatic polyurethane acrylate, tetrafunctional aliphatic polyurethane acrylate, and hexafunctional aliphatic polyurethane acrylate, or a combination of several thereof.

[0008] In a preferred embodiment, the polyester acrylate is any one of difunctional polyester acrylate, trifunctional polyester acrylate, tetrafunctional polyester acrylate, hexafunctional polyester acrylate, or a combination of several thereof.

[0009] In a preferred embodiment, the long carbon chain aliphatic polyurethane acrylate having 12 to 18 carbon atoms is any one of difunctional aliphatic polyurethane acrylate, trifunctional aliphatic polyurethane acrylate, tetrafunctional aliphatic polyurethane acrylate, and hexafunctional aliphatic polyurethane acrylate, or a combination of several thereof.

[0010] In a preferred embodiment, the bifunctional acrylate monomer is any one of 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, and tripropylene glycol diacrylate, or a combination of several of them.

[0011] In a preferred embodiment, the trifunctional acrylate monomer is trimethylolpropane triacrylate and / or propoxylated trimethylolpropane triacrylate.

[0012] In a preferred embodiment, the photoinitiator is 1-hydroxycyclohexyl phenyl ketone.

[0013] The method for preparing the UV curing glue described in any of the above schemes comprises the following steps: S1, mixing the difunctional acrylate monomer and the trifunctional acrylate monomer, adding the photoinitiator, and mixing evenly; S2, adding the aliphatic polyurethane acrylate having 4 to 8 carbon atoms to the mixture obtained in step S1, stirring until completely dispersed, then adding the polyester acrylate and stirring until completely dispersed, and continuing to add the long-chain aliphatic polyurethane acrylate having 12 to 18 carbon atoms and stirring until completely dispersed; S3, adding the silane coupling agent modified fumed silica to the mixture obtained in step S2, stirring until uniformly dispersed; and standing in a dark place to obtain UV glue.

[0014] When the ultraviolet curing glue provided by the present invention is used to prepare the IMR film, the curing speed is fast, the adhesion is good, the flexibility is high, the tensile strength is large, and a pattern with a better effect can be presented to the greatest extent.

[0015] Compared with the prior art, the technical solution of the present invention has the following beneficial effects: (1) The UV glue provided in the present invention as a coating for UV molding not only has a fast curing speed and a transparent appearance, but also has excellent adhesion, flexibility (elongation at break ≥55%, bending stiffness ≥0.82mN·m) and tensile strength, which can better ensure the injection molding quality and make the pattern present a more perfect effect.

[0016] (2) Since the UV glue of the present invention has a faster curing speed, it can reduce the volatilization of the glue, thereby reducing the amount of glue used and reducing the production cost of the IMR film. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a flow chart of preparing IMR film using UV glue; Figure 2 Schematic diagram of the structure of the holographic film prepared using UV glue.

[0018] In the figure: 1. Base film; 2. Pre-coating layer; 3. UV adhesive coating layer; 4. Mold; 5. UV adhesive coating layer with pattern; 6. Release layer. DETAILED DESCRIPTION

[0019] The following content is combined with the embodiments to clearly and completely describe the technical solution of the present application so that those skilled in the art can fully understand the present application. Obviously, the described embodiments are only some preferred embodiments of the present application, rather than all embodiments. Any equivalent transformation or substitution made to the following implementation modes by those of ordinary skill in the art without creative work belongs to the protection scope of the present application.

[0020] A specific embodiment of the present invention provides an ultraviolet curing glue (or UV glue), comprising the following components in parts by mass: 15 to 25 parts of aliphatic polyurethane acrylate with 4 to 8 carbon atoms, 15 to 25 parts of polyester acrylate, 10 to 15 parts of long carbon chain aliphatic polyurethane acrylate with 12 to 18 carbon atoms, 2 to 6 parts of silane coupling agent modified fumed silica, 30 to 35 parts of difunctional acrylate monomers, 5 to 10 parts of trifunctional acrylate monomers, and 4 to 8 parts of photoinitiator.

[0021] The preparation method of the UV glue comprises the following steps: S1, mixing the difunctional acrylate monomer and the trifunctional acrylate monomer, adding the photoinitiator, and mixing evenly; S2, adding the aliphatic polyurethane acrylate having 4 to 8 carbon atoms to the mixture obtained in step S1, stirring until completely dispersed, then adding the polyester acrylate and stirring until completely dispersed, and continuing to add the long-chain aliphatic polyurethane acrylate having 12 to 18 carbon atoms and stirring until completely dispersed; S3, adding the silane coupling agent modified fumed silica to the mixture obtained in step S2, stirring until uniformly dispersed; and standing in a dark place for 12 hours to obtain UV glue.

[0022] As an example, the aliphatic polyurethane acrylate with 4 to 8 carbon atoms is any one or a combination of difunctional aliphatic polyurethane acrylate, trifunctional aliphatic polyurethane acrylate, tetrafunctional aliphatic polyurethane acrylate, and hexafunctional aliphatic polyurethane acrylate. For example, the aliphatic polyurethane acrylate with 4 to 8 carbon atoms is any one or a combination of CN9006NS of Sartomer, 6106 of Changxing Materials Industry Co., Ltd., and 6130B-80 of Changxing Materials Industry Co., Ltd.

[0023] As an example, the amount of the aliphatic polyurethane acrylate having 4 to 8 carbon atoms is 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts or 25 parts.

[0024] As an example, the polyester acrylate is any one or a combination of difunctional polyester acrylate, trifunctional polyester acrylate, tetrafunctional polyester acrylate, hexafunctional polyester acrylate. For example, the polyester acrylate is any one or a combination of CN8010 of Sartomer, 61438 of Changxing Materials Industry Co., Ltd., and 6145-100H of Changxing Materials Industry Co., Ltd.

[0025] As an example, the polyester acrylate is present in an amount of 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts or 25 parts.

[0026] As an example, the long carbon chain aliphatic polyurethane acrylate with 12 to 18 carbon atoms is any one of difunctional aliphatic polyurethane acrylate, trifunctional aliphatic polyurethane acrylate, tetrafunctional aliphatic polyurethane acrylate, and hexafunctional aliphatic polyurethane acrylate, or a combination thereof. For example, the long carbon chain aliphatic polyurethane acrylate with 12 to 18 carbon atoms is any one of CR92452 of Guangdong Haohui New Materials Co., Ltd., CR91908 of Guangdong Haohui New Materials Co., Ltd., and 6150-100 of Changxing Materials Industry Co., Ltd., or a combination thereof.

[0027] As an example, the amount of the long carbon chain aliphatic polyurethane acrylate having 12 to 18 carbon atoms is 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts.

[0028] As an example, the amount of the silane coupling agent-modified fumed silica is 2 parts, 3 parts, 4 parts, 5 parts or 6 parts.

[0029] As an example, the bifunctional acrylate monomer is any one of 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, and tripropylene glycol diacrylate, or a combination of several of them.

[0030] As an example, the amount of the difunctional acrylate monomer is 30 parts, 31 parts, 32 parts, 33 parts, 34 parts or 35 parts.

[0031] As an example, the trifunctional acrylate monomer is trimethylolpropane triacrylate and / or propoxylated trimethylolpropane triacrylate.

[0032] As an example, the amount of the trifunctional acrylate monomer is 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts.

[0033] As an example, the photoinitiator is 1-hydroxycyclohexyl phenyl ketone.

[0034] As an example, the photoinitiator is present in an amount of 4 parts, 5 parts, 6 parts, 7 parts or 8 parts.

[0035] like Figure 1As shown, the method for preparing an IMR (In-Mould Decoration by Roller) master film using the UV glue comprises the following steps: coating a polyurethane emulsion on a base film 1 having a thickness of 30 to 35 μm to obtain a pre-coating layer 2 having a thickness of 2 to 4 μm. Coating the UV glue on the surface of the pre-coating layer 2 to obtain a UV glue coating layer 3 having a thickness of 4 to 16 μm. Aligning a side of a mold 4 (e.g., a nickel plate) with a pattern on it to the UV glue coating layer 3, applying pressure, and curing the UV glue coating layer 3 under ultraviolet light, thereby transferring the pattern on the mold 4 to the UV glue coating layer 3 to obtain a UV glue coating layer 5 with a pattern. Removing the mold to obtain an IMR film.

[0036] As an example, the material of the base film is any one of PET (polyethylene terephthalate), PVC (polyvinyl chloride), and PC (polycarbonate).

[0037] As an example, the base film has a thickness of 30 μm, 31 μm, 32 μm, 33 μm, 34 μm or 35 μm.

[0038] As an example, the polyurethane emulsion is Joncryl ® Polyurethane emulsion 586, BASF's Joncryl ® Polyurethane emulsion 611, BASF's Joncryl ® Any one of the polyurethane emulsions 682 or a combination of several of them.

[0039] As an example, the thickness of the pre-coating layer is 2 μm, 3 μm, or 4 μm.

[0040] As an example, the thickness of the UV adhesive coating is 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or 16 μm.

[0041] The aliphatic polyurethane acrylate with a carbon number of 4 to 8 used in the following embodiments is a product produced by Sadomer, Inc. of the United States, and its product model is hexafunctional aliphatic polyurethane acrylate oligomer CN9006NS. The polyester acrylate used is a product produced by Sadomer, Inc. of the United States, and its product model is difunctional polyester acrylate CN8010. The long-chain aliphatic polyurethane acrylate with a carbon number of 12 to 18 used is a product produced by Guangdong Haohui New Materials Co., Ltd., and its product model is difunctional aliphatic polyurethane acrylate CR92452. The photoinitiator 1-hydroxycyclohexyl phenyl ketone (IRG-184) used is a product of BASF. The silane coupling agent modified fumed silica used is AEROSIL, a product of Evonik of Germany. ®R 7200. The methods not described in detail in the following examples are conventional methods well known to those skilled in the art.

[0042] Example 1 A UV curing glue (or UV glue) comprises the following components in parts by mass: 25 parts of aliphatic polyurethane acrylate with 4 to 8 carbon atoms (CN9006NS), 15 parts of polyester acrylate (CN8010), 12 parts of long carbon chain aliphatic polyurethane acrylate with 12 to 18 carbon atoms (CR92452), 3 parts of silane coupling agent modified fumed silica, 15 parts of 1,6-hexanediol diacrylate, 15 parts of tripropylene glycol diacrylate, 10 parts of trihydroxymethylpropane triacrylate, and 5 parts of 1-hydroxycyclohexyl phenyl ketone (IRG-184).

[0043] The preparation method of the UV glue comprises the following steps: S1. Mix 1,6-hexanediol diacrylate, tripropylene glycol diacrylate and trihydroxymethylpropane triacrylate, add a photoinitiator, and mix well (for example, stirring at 100 rpm for 10 min); S2. Add aliphatic polyurethane acrylate (CN9006NS) having 4 to 8 carbon atoms to the mixture obtained in step S1, stir until completely dispersed (e.g., stir at 100 rpm for 15 min), add polyester acrylate (CN8010) and stir until completely dispersed (e.g., stir at 100 rpm for 15 min), continue to add long-chain aliphatic polyurethane acrylate (CR92452) having 12 to 18 carbon atoms and stir until completely dispersed (e.g., stir at 100 rpm for 15 min); S3, adding silane coupling agent modified fumed silica to the mixture obtained in step S2, stirring until uniformly dispersed; and standing in a dark place for 12 hours to obtain UV glue.

[0044] The method for preparing an IMR film using the UV glue comprises the following steps: coating Joncryl on a base film (the base film is made of PET) with a thickness of 35 μm; ® Polyurethane emulsion 586 is used to obtain a pre-coating layer with a thickness of 2 μm. The UV glue is applied on the surface of the pre-coating layer to obtain a UV glue coating layer with a thickness of 10 μm. The side of the mold (e.g., nickel plate) with the pattern is aligned with the UV glue coating layer, and pressure is applied to cure the UV glue coating layer under ultraviolet light, so that the pattern on the mold is transferred to the UV glue coating layer. The mold is removed to obtain an IMR film.

[0045] Example 2 A UV curing glue (or UV glue) comprises the following components in parts by mass: 15 parts of aliphatic polyurethane acrylate with 4 to 8 carbon atoms (CN9006NS), 25 parts of polyester acrylate (CN8010), 10 parts of long carbon chain aliphatic polyurethane acrylate with 12 to 18 carbon atoms (CR92452), 5 parts of silane coupling agent modified fumed silica, 15 parts of 1,6-hexanediol diacrylate, 15 parts of tripropylene glycol diacrylate, 10 parts of propoxylated trimethylolpropane triacrylate, and 5 parts of 1-hydroxycyclohexyl phenyl ketone (IRG-184).

[0046] The preparation method of the UV glue is basically the same as that in Example 1, except that, step S1: S1. Mix 1,6-hexanediol diacrylate, tripropylene glycol diacrylate and propoxylated trimethylolpropane triacrylate evenly, add a photoinitiator, and mix evenly (for example, stirring at 100 rpm for 10 min).

[0047] The method for preparing an IMR film using the UV glue comprises the following steps: coating Joncryl on a base film (the base film is made of PET) with a thickness of 35 μm; ® Polyurethane emulsion 611 is used to obtain a pre-coating with a thickness of 3 μm. The UV glue is applied on the surface of the pre-coating to obtain a UV glue coating with a thickness of 14 μm. The side of the mold (e.g., nickel plate) with the pattern is aligned with the UV glue coating, and pressure is applied to cure the UV glue coating under ultraviolet light, so that the pattern on the mold is transferred to the UV glue coating. The mold is removed to obtain an IMR film.

[0048] Example 3 A UV curing glue (or UV glue) comprises the following components in parts by mass: 20 parts of aliphatic polyurethane acrylate with 4 to 8 carbon atoms (CN9006NS), 15 parts of polyester acrylate (CN8010), 15 parts of long carbon chain aliphatic polyurethane acrylate with 12 to 18 carbon atoms (CR92452), 4 parts of silane coupling agent modified fumed silica, 15 parts of 1,6-hexanediol dimethacrylate, 20 parts of tripropylene glycol diacrylate, 5 parts of trimethylolpropane triacrylate, and 6 parts of 1-hydroxycyclohexyl phenyl ketone (IRG-184).

[0049] The preparation method of the UV glue is basically the same as that in Example 1, except that, step S1: S1. Mix 1,6-hexanediol dimethacrylate, tripropylene glycol diacrylate and trimethylolpropane triacrylate evenly, add a photoinitiator, and mix evenly (for example, stirring at 100 rpm for 10 min).

[0050] The method for preparing an IMR film using the UV glue comprises the following steps: coating Joncryl on a base film (the base film is made of PET) with a thickness of 38 μm; ® Polyurethane emulsion 682 is used to obtain a pre-coating with a thickness of 4 μm. The UV glue is applied on the surface of the pre-coating to obtain a UV glue coating with a thickness of 12 μm. The side of the mold (e.g., nickel plate) with the pattern is aligned with the UV glue coating, and pressure is applied to cure the UV glue coating under ultraviolet light, so that the pattern on the mold is transferred to the UV glue coating. The mold is removed to obtain an IMR film.

[0051] Example 4 A UV curing glue (or UV glue) comprises the following components in parts by mass: 15 parts of aliphatic polyurethane acrylate with 4 to 8 carbon atoms (CN9006NS), 20 parts of polyester acrylate (CN8010), 10 parts of long carbon chain aliphatic polyurethane acrylate with 12 to 18 carbon atoms (CR92452), 6 parts of silane coupling agent modified fumed silica, 20 parts of 1,6-hexanediol dimethacrylate, 15 parts of tripropylene glycol diacrylate, 10 parts of trimethylolpropane triacrylate, and 4 parts of 1-hydroxycyclohexyl phenyl ketone (IRG-184).

[0052] The preparation method of the UV glue is the same as that in Example 1.

[0053] The method for preparing an IMR film using the UV glue comprises the following steps: coating Joncryl on a base film (the base film is made of PET) with a thickness of 50 μm; ® Polyurethane emulsion 586 is used to obtain a pre-coating with a thickness of 3 μm. The UV glue is applied on the surface of the pre-coating to obtain a UV glue coating with a thickness of 16 μm. The side of the mold (e.g., nickel plate) with the pattern is aligned with the UV glue coating, and pressure is applied to cure the UV glue coating under ultraviolet light, so that the pattern on the mold is transferred to the UV glue coating. The mold is removed to obtain an IMR film.

[0054] It is understandable that the UV glue prepared in the embodiment can also be used to prepare an IMR holographic film with a release layer. Figure 2 As shown, the structure of the IMR holographic film includes a base film 1, a release layer 6 and a UV adhesive coating 5 with a pattern stacked in sequence (the UV adhesive coating is obtained by UV curing the UV glue prepared in the embodiment, and the pattern is obtained by mold transfer). After injection molding, the UV adhesive coating will remain on the surface of the injection molded part. Among them, the material of the release layer 6 is the same as Figure 1 The material of the middle pre-coat layer 2 is the same.

[0055] Comparative Example 1 A UV curing glue (or UV glue) comprises the following components in parts by mass: 25 parts of aliphatic polyurethane acrylate with 4 to 8 carbon atoms (CN9006NS), 15 parts of polyester acrylate (CN8010), 3 parts of silane coupling agent modified fumed silica, 15 parts of 1,6-hexanediol diacrylate, 15 parts of tripropylene glycol diacrylate, 10 parts of trihydroxymethylpropane triacrylate, and 5 parts of 1-hydroxycyclohexyl phenyl ketone (IRG-184).

[0056] The composition of the UV glue in this comparative example is different from that in Example 1 in that it does not contain a long carbon chain aliphatic polyurethane acrylate (CR92452) with a carbon number of 12 to 18. The preparation method of the UV glue is basically the same as that in Example 1, except that the long carbon chain aliphatic polyurethane acrylate (CR92452) with a carbon number of 12 to 18 is not added in step S2.

[0057] Comparative Example 2 A UV curing glue (or UV glue) comprises the following components in parts by mass: 15 parts of aliphatic polyurethane acrylate with 4 to 8 carbon atoms (CN9006NS), 25 parts of polyester acrylate (CN8010), 10 parts of long carbon chain aliphatic polyurethane acrylate with 12 to 18 carbon atoms (CR92452), 5 parts of fumed silica, 15 parts of 1,6-hexanediol diacrylate, 15 parts of tripropylene glycol diacrylate, 10 parts of propoxylated trimethylolpropane triacrylate, and 5 parts of 1-hydroxycyclohexyl phenyl ketone (IRG-184).

[0058] The composition of the UV glue in this comparative example is different from that in Example 2 in that ordinary fumed silica is used instead of silane coupling agent modified fumed silica. The preparation method of the UV glue is basically the same as that in Example 2, except that ordinary fumed silica is added in step S3.

[0059] Comparative Example 3 A UV curing glue (or UV glue) comprises the following components in parts by mass: 20 parts of aliphatic polyurethane acrylate with 4 to 8 carbon atoms (CN9006NS), 15 parts of polyester acrylate (CN8010), 15 parts of long carbon chain aliphatic polyurethane acrylate with 12 to 18 carbon atoms (CR92452), 15 parts of 1,6-hexanediol dimethacrylate, 20 parts of tripropylene glycol diacrylate, 5 parts of trimethylolpropane triacrylate, and 6 parts of 1-hydroxycyclohexyl phenyl ketone (IRG-184).

[0060] The composition of the UV glue in this comparative example is different from that in Example 3 in that the UV glue does not contain silane coupling agent-modified fumed silica. The preparation method of the UV glue is substantially the same as that in Example 3, except that no silica in any form is added in step S3.

[0061] Comparative Example 4 A UV curing glue (or UV glue) comprises the following components in parts by mass: 15 parts of aliphatic polyurethane acrylate with 4 to 8 carbon atoms (CN9006NS), 20 parts of polyester acrylate (CN8010), 10 parts of long carbon chain aliphatic polyurethane acrylate with 12 to 18 carbon atoms (CR92452), 6 parts of silane coupling agent modified fumed silica, and 4 parts of 1-hydroxycyclohexyl phenyl ketone (IRG-184).

[0062] The composition of the UV glue in this comparative example is different from that in Example 4 in that the UV glue does not contain difunctional acrylate monomers and trifunctional acrylate monomers. The preparation method of the UV glue is basically the same as that of Example 4, except that difunctional acrylate monomers and trifunctional acrylate monomers are not added in step S1.

[0063] UV glue performance test 1. Light curing rate test The photocuring rate is measured by the photocuring time (seconds, s). The UV glue prepared in Examples 1 to 4 and Comparative Examples 1 to 4 was evenly coated on a 50 μm thick base film (made of PET), cured under a HOK4 / 120 (400W) UV lamp, and its surface drying time was measured by a dry method. When the pencil hardness of the cured film reaches a certain level, the shortest time during which the hardness of the cured film does not change by continuing to extend the illumination time is called the curing time. The pencil hardness is measured according to the method in GB / T 6739-2022 "Determination of paint film hardness by pencil method for paints and varnishes".

[0064] 2. Adhesion test According to the cross-cut test specified in GB / T 9286-2021 "Scratch test for paints and varnishes", the sample surface is cut manually with a cutting interval of 2mm on the smooth part of the paint film surface, and the coating adhesion is required to be no less than Grade 0.

[0065] 3. Tensile strength test The tensile strength is measured by the elongation at break when any slight change in the appearance of the cured UV adhesive coating surface (cracks, light-transmitting spots, etc.) is observed. The elongation at break is tested using a microcomputer-controlled high-temperature universal material testing machine CTM-05G / 500N.

[0066] 4. Flexibility test The flexibility of the material is measured by bending stiffness. Bending angle: 15°, bending length 50mm, basis weight: 50g / m 2 , Direction: longitudinal direction of UV glue coating surface, Number of bending times: 1, tested on PY-H609 plastic film sheet material bending stiffness instrument.

[0067] The above test results are shown in Table 1.

[0068] Table 1 UV glue performance test results

[0069] As can be seen from Table 1, the UV glue prepared in Comparative Example 1 does not contain a long carbon chain aliphatic polyurethane acrylic resin, and its elongation at break and bending stiffness are significantly reduced, and the adhesion is basically unaffected. The UV glue prepared by ordinary fumed silica in Comparative Example 2 is basically unaffected in adhesion, the curing speed is significantly slowed down, and the elongation at break and bending stiffness are significantly reduced compared to the UV glue prepared by silane coupling agent modified fumed silica in Example 2. The UV glue prepared in Comparative Example 3 does not contain silica, its adhesion is unqualified, the curing speed is extremely slow, the elongation at break drops sharply, and the bending stiffness is also significantly reduced. The UV glue prepared in Comparative Example 4 does not contain difunctional acrylate monomers and trifunctional acrylate monomers, and its bending stiffness is significantly reduced (bending stiffness refers to the ability of the film to resist bending deformation and maintain its original shape or only slightly deform under a certain external force), and the decrease in bending stiffness will cause cracks on the surface of the product after the final injection molding and demolding.

[0070] The main reasons for the above results are: (1) The molecular chain of long-chain aliphatic polyurethane acrylate with 12 to 18 carbon atoms contains a longer carbon chain, which enables the resin molecules to form a more flexible network structure after curing. This flexible network structure helps to relieve external stress, thereby improving the flexibility of the UV adhesive coating.

[0071] (2) The silane coupling agent modified fumed silica used in this application has a positive effect on improving the photocuring rate, flexibility, tensile strength and adhesion. The main reasons are as follows: (a) The surface of ordinary fumed silica is hydrophilic. After being modified by a silane coupling agent, the hydrophilicity is transformed into hydrophobicity, thereby increasing the compatibility between the main resins (aliphatic polyurethane acrylates with 4 to 8 carbon atoms, polyester acrylates, and long carbon chain aliphatic polyurethane acrylates with 12 to 18 carbon atoms), reducing agglomeration, and promoting uniform dispersion, so that the photoinitiator can more effectively absorb ultraviolet light and initiate polymerization. At the same time, the modified fumed silica can improve the optical properties of UV glue (such as light transmittance), allowing ultraviolet light to penetrate the glue layer more deeply, promote internal polymerization reactions, and increase the photocuring rate. (b) The molecular structure of silane coupling agent-modified fumed silica contains functional groups (such as methacryloyloxy) that can react with the main resin. These functional groups react chemically with the resin molecular chain and form chemical bonds. This chemical bonding not only enhances the interfacial bonding between fumed silica and the resin, but also enables the two to share stress when subjected to external forces, thereby improving the overall flexibility. In addition to chemical bonding, silane coupling agents may also interact with the resin matrix through intermolecular forces such as hydrogen bonds, further enhancing the interfacial bonding strength and improving the flexibility of UV glue. (c) Silane coupling agent-modified fumed silica particles may form a three-dimensional network structure in the resin matrix. This network structure can increase the toughness and elastic recovery of the material, allowing it to more effectively resist deformation and fracture when subjected to tensile force. At the same time, when the material is subjected to tensile force and cracks are generated, the fumed silica particles can act as a physical barrier to prevent the cracks from further expanding. Therefore, the UV glue prepared in this application has both excellent flexibility and better tensile strength.

[0072] (3) The trifunctional acrylate monomer added to the UV glue prepared in this application has the advantages of fast curing speed and good dilution effect, and can effectively adjust the viscosity of the UV glue to meet the process requirements. In addition, there are multiple acrylate groups in the trifunctional acrylate monomer molecule, and these groups will repel each other during the curing process, forming a certain steric hindrance. This steric hindrance effect helps to alleviate the stress concentration in the cross-linked network, thereby improving the flexibility of the glue.

[0073] The above-described embodiments are only preferred embodiments of the present application and are not intended to limit the scope of protection of the present application. For any person skilled in the art, the present application may have various changes and modifications. Any simple equivalent changes and modifications made based on the scope of protection of the present application and the contents of the specification should be included in the scope of protection of the present application.

Claims

1. A UV curing glue, characterized in that: The invention comprises the following components in parts by mass: 15-25 parts of aliphatic polyurethane acrylate having 4-8 carbon atoms, 15-25 parts of polyester acrylate, 10-15 parts of long carbon chain aliphatic polyurethane acrylate having 12-18 carbon atoms, 2-6 parts of silane coupling agent modified fumed silica, 30-35 parts of difunctional acrylate monomer, 5-10 parts of trifunctional acrylate monomer and 4-8 parts of photoinitiator.

2. The UV curing glue according to claim 1, characterized in that: The aliphatic polyurethane acrylate having 4 to 8 carbon atoms is any one of difunctional aliphatic polyurethane acrylate, trifunctional aliphatic polyurethane acrylate, tetrafunctional aliphatic polyurethane acrylate and hexafunctional aliphatic polyurethane acrylate or a combination of several thereof.

3. The UV curing glue according to claim 1, characterized in that: The polyester acrylate is any one of difunctional polyester acrylate, trifunctional polyester acrylate, tetrafunctional polyester acrylate, hexafunctional polyester acrylate or a combination of several thereof.

4. The UV curing glue according to claim 1, characterized in that: The long carbon chain aliphatic polyurethane acrylate with 12 to 18 carbon atoms is any one of difunctional aliphatic polyurethane acrylate, trifunctional aliphatic polyurethane acrylate, tetrafunctional aliphatic polyurethane acrylate and hexafunctional aliphatic polyurethane acrylate or a combination of several thereof.

5. The UV curing glue according to claim 1, characterized in that: The bifunctional acrylate monomer is any one of 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, and tripropylene glycol diacrylate, or a combination of several of them.

6. The UV curing glue according to claim 1, characterized in that: The trifunctional acrylate monomer is trimethylolpropane triacrylate and / or trimethylolpropane propoxide triacrylate.

7. The UV curing glue according to claim 1, characterized in that: The photoinitiator is 1-hydroxycyclohexyl phenyl ketone.

8. The method for preparing the UV curing glue according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, mixing the difunctional acrylate monomer and the trifunctional acrylate monomer, adding the photoinitiator, and mixing evenly; S2, adding the aliphatic polyurethane acrylate having 4 to 8 carbon atoms to the mixture obtained in step S1, stirring until completely dispersed, then adding the polyester acrylate and stirring until completely dispersed, and continuing to add the long-chain aliphatic polyurethane acrylate having 12 to 18 carbon atoms and stirring until completely dispersed; S3, adding the silane coupling agent modified fumed silica to the mixture obtained in step S2, stirring until uniformly dispersed; and standing in a dark place to obtain UV glue.

9. Use of the UV curing glue according to any one of claims 1 to 7 in the preparation of IMR diaphragms.

10. An IMR film comprising the UV-curable glue according to any one of claims 1 to 7.